Neutrophil-mediated immune dysregulation in recurrent miscarriage: implications of APP–CD74 signaling and CXCL1 as diagnostic biomarkers - He, Shan; Ma, Fei; Yu, Meng; Wu, Jia-man; Gong, You-ming; Luo, Ke-wang; Chang, Hong; Liang, Qi; Ning, Yan (Frontiers in Immunology, 2025)
BackgroundRecurrent miscarriage (RM), characterized by the loss of two or more consecutive pregnancies, is a significant challenge in reproductive medicine. While immunological dysregulation is increasingly recognized as a key contributor, the role of innate immunity, particularly neutrophils, remains underexplored. Understanding neutrophil-driven immune mechanisms may provide novel diagnostic and therapeutic insights for RM.MethodsWe integrated bulk transcriptomic datasets from RM, autoimmune diseases, and decidua single-cell RNA sequencing data. Differentially expressed genes (DEGs) and enriched pathways were identified, and intercellular communication was analyzed using CellChat. Key genes (KGs) were validated through ROC analysis, nomogram modeling, and experimental validation in trophoblast cells.ResultsSingle-cell profiling revealed increased neutrophil proportions and distinct activation states in RM. Neutrophils exhibited a TNF-α-driven polarized phenotype with upregulated oxidative stress and antigen presentation. Intercellular communication analysis identified the APP-CD74 axis as a key signaling pathway. CXCL1 and related genes were consistently upregulated and showed strong diagnostic performance. Molecular docking identified potential therapeutic compounds targeting CXCL1, and in vitro assays confirmed immune-mediated trophoblast injury.ConclusionsNeutrophil-driven immune dysregulation, with TNF-α-polarized neutrophils and APP–CD74 signaling, contributes to RM pathogenesis. CXCL1 and related genes serve as promising biomarkers, offering new opportunities for early diagnosis and therapeutic intervention.